2014
DOI: 10.4291/wjgp.v5.i3.122
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms and Helicobacter pylori: Dissemination and persistence within the environment and host

Abstract: The presence of viable Helicobacter pylori (H. pylori) in the environment is considered to contribute to the levels of H. pylori found in the human population, which also aids to increase its genetic variability and its environmental adaptability and persistence. H. pylori form biofilms both within the in vitro and in vivo environment. This represents an important attribute that assists the survival of this bacterium within environments that are both hostile and adverse to proliferation. It is the aim of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 0 publications
0
43
0
2
Order By: Relevance
“…These authors have thus suggested the ability of H. pylori to produce self-inhibiting substances with bacteriostatic activity. It appears, however, that the effect of the apparent inhibition of the bacteria was due to the transition of the microorganisms into the VBNC state, which in the case of H. pylori is connected with spiral-to-coccoid transformation (9,10,14,22,33). Cis-2-tetradecenic acid (C 14 :Δ 2 ), which is produced by X. fastidiosa, is responsible for biofilm formation and autoaggregative behavior associated with the increased synthesis of hemagglutinin-like HxfA/B proteins.…”
Section: Communication Of Microorganisms Via Diffusible Signal Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…These authors have thus suggested the ability of H. pylori to produce self-inhibiting substances with bacteriostatic activity. It appears, however, that the effect of the apparent inhibition of the bacteria was due to the transition of the microorganisms into the VBNC state, which in the case of H. pylori is connected with spiral-to-coccoid transformation (9,10,14,22,33). Cis-2-tetradecenic acid (C 14 :Δ 2 ), which is produced by X. fastidiosa, is responsible for biofilm formation and autoaggregative behavior associated with the increased synthesis of hemagglutinin-like HxfA/B proteins.…”
Section: Communication Of Microorganisms Via Diffusible Signal Factorsmentioning
confidence: 99%
“…This is supported by chemotaxis away from AI-2 and protons and towards nutrients (amino acids and metal ions), urea, and HCO 3 -. In addition, the spiral shape enables effective penetration of mucin (6,22,31). After bacterial proliferation in the gastric mucosa, microorganisms enter the stationary phase accompanied by a decrease in AI-2 concentration and an increase in DSFs autoinductive activity.…”
Section: The Holistic Model Of H Pylori Infectionmentioning
confidence: 99%
See 3 more Smart Citations